Learning legal rules : - Holland, James A. (Oxford University Press, 2006)
1. Understanding the law; 2. Finding the law; 3. Reading the law; 4. Law, fact, and language; 5. The doctrine of judicial precedent; 6. How precedent operates: ratio decidendi and obiter dictum; 7. Making sense of statutes; 8. Interpreting statutes; 9. 'Bringing rights home': legal method and convention rights; 10. European legal method; 11. Exploiting legal reasoning.